The Rho-associated kinase inhibitor fasudil can replace Y-27632 for use in human pluripotent stem cell research - So, Seongjun; Lee, Yeonmi; Choi, Jiwan; Kang, Seoon; Lee, Ji-Yoon; Hwang, Julie; Shin, Joosung; Dutton, James R.; Seo, Eul-Ju; Lee, Beom Hee; Kim, Chong Jai; Mitalipov, Shoukhrat; et al. (PLOS ONE, 2020)
Poor survival of human pluripotent stem cells (hPSCs) following freezing, thawing, or passaging hinders the maintenance and differentiation of stem cells. Rho-associated kinases (ROCKs) play a crucial role in hPSC survival. To date, a typical ROCK inhibitor, Y-27632, has been the primary agent used in hPSC research. Here, we report that another ROCK inhibitor, fasudil, can be used as an alternative and is cheaper than Y-27632. It increased hPSC growth following thawing and passaging, like Y-27632, and did not affect pluripotency, differentiation ability, and chromosome integrity. Furthermore, fasudil promoted retinal pigment epithelium (RPE) differentiation and the survival of neural crest cells (NCCs) during differentiation. It was also useful for single-cell passaging of hPSCs and during aggregation. These findings suggest that fasudil can replace Y-27632 for use in stem research.